ANALYSIS OF SERVICE QUALITY TO CUSTOMER SATISFACTION AT IBIS SENEN HOTEL JAKARTA - Sannindra, Akristi Eni; Tarigan, Eviana; Nugraha, Rizki Nurul (Jurnal Manajemen Pelayanan Hotel, 2022)
In the global era world business is intense with competition, especially in the field of hospitality services company. Hotel is a company managed by its owner to provide food service, drinks, and a room for sleeping facilities to people who are traveling and able to pay with a reasonable amount of care received in accordance with the absence of a special agreement. Quality of service and facilities at this time, more emphasis in the business world for allegedly affects customer satisfaction, and will also take into account competition arising from a variety of hospitality services. Facilities used by each company a variety of forms, types and benefits. The purpose of this study to analyze the impact of service quality and customer satisfaction at the facilities of the hotel in the city Ibis Senen Jakarta. Library research methods, give the results and showed the quality of services and facilities affects customer satisfaction. Ibis Senen hotel management should improve customer satisfaction as to the quality of service is better, and provide affordable facilities so that consumers will be back to stay. Keywords: Quality of Service, Hotel and Customer